2019
DOI: 10.1523/eneuro.0179-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single Cage Housing on Stress, Cognitive, and Seizure Parameters in the Rat and Mouse Pilocarpine Models of Epilepsy

Abstract: Significance Statement Many experimental approaches require housing rodents in individual cages, a stressful condition for social animals, even in an enriched environment context. Using the pilocarpine (pilo) model of epilepsy in rats and mice, we report that singly housing animals develop a more severe phenotype in terms of stress and epilepsy as compared to animals maintaining social contact. We propose that social isolation adds a degree of complexity for the interpretation of data, which may be particularl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 73 publications
4
106
0
Order By: Relevance
“…All mice were group-housed (four to six per cage) prior to surgery under a 12 h light-dark cycle (light on from 8:00 a.m. to 8:00 p.m.) with ad libitum access to food and water. The mice were individually housed after surgery for a better recovery and meanwhile reducing the failure rate of electrodes implantation, although singly housed animals showed stress and worse epilepsy phenotype 64 . All behavior experiments were performed each day between 9:00 a.m. and 7:00 p.m.…”
Section: Methodsmentioning
confidence: 99%
“…All mice were group-housed (four to six per cage) prior to surgery under a 12 h light-dark cycle (light on from 8:00 a.m. to 8:00 p.m.) with ad libitum access to food and water. The mice were individually housed after surgery for a better recovery and meanwhile reducing the failure rate of electrodes implantation, although singly housed animals showed stress and worse epilepsy phenotype 64 . All behavior experiments were performed each day between 9:00 a.m. and 7:00 p.m.…”
Section: Methodsmentioning
confidence: 99%
“…Due to an increase in corticosterone levels and anxiety behaviors previously observed in mice during forced exercise studies, which may interfere with any exercise benefits, we chose voluntary running using a running wheel [13]. Although the voluntary running paradigm necessitated housing animals individually, which has been shown to increase stress in some studies while decreasing it in others, wheel running ensured that the exercise itself would not induce stress and allows for both a direct measurement of running distance (for a single animal) and more opportunity for exercise (without competition) [24,25]. Additionally, many different strains of non-mutant laboratory mice display large increases in hippocampal neurogenesis from running when singly housed [21], so the effect of social isolation on exercise-induced brain adaptations in mice is not sufficient to outweigh certain benefits.…”
Section: Plos Onementioning
confidence: 99%
“…The reason for this high rate of USV vocalizing animals in the present study might be related to their housing condition, as animals implanted with electrodes were housed individually. It has been shown that single housing increases anxiety and biological markers of stress as compared to social housing (Arakawa, 2018;Manouze et al, 2019) and the amount of USV emission is enhanced when the level of anxiety is increased (Wöhr et al, 2005). Indeed, more anxious rats (as assessed through the elevated plus maze) were shown to exhibit more freezing and to be more likely to vocalize than less anxious animals (Borta et al, 2006).…”
Section: Interval Timing and Level Of Stressmentioning
confidence: 99%